Comunicación y pensamiento comprensivo: el abrazo inclusivo de la comprensión como método - Künsch, Dimas A.; Passos, Mateus Yuri; Osorio Vargas, Raúl (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This essay focuses in clarifying our understanding of “comprehension” and our notion of comprehension as a method among the scholarly studies and researches of the research group “Of comprehension as a method”. We also discuss the body of texts published in the special edition of the Folios journal (nº 39 - jan.-jun. 2018) that features as its subject “Thinking under the sign of comprehension”, in order to understand how different authors suggest or propose a link between their work and the perspective of comprehensive thinking. Essay writing is featured in the work of the research group as a methodological option for a genre which, when not poorly performed, presents itself as a dialogical, conversational, comprehensive mode of writing.